BOOK REVIEW: GOD AND THE PANDEMIC. A CHRISTIAN REFLECTION ON THE CORONAVIRUS AND ITS AFTERMATH - M. Laubscher (Acta Theologica)
Wright, N.T. (Grand Rapids, MI: Zondervan, 2020), 96 pp. Price: R220, ISBN: 978-0-310-12080-3 is reviewed by M. Laubscher.